Síntesis verde de nanopartículas de hierro cero valente para la remoción de cadmio, cromo y arsénico en solución (2020)
Zero-valent iron (ZVI) nanoparticles are highly versatile in environmental remediation processes. In this study, the different methods of synthesis and modifications of nHCV are presented, the comparison made between the methods of chemical reduction and green synthesis. Stabilized nanoparticles of approximately 90 nm in diameter were synthesized. Their respective characterization is presented, as well as their adsorbent and reducing capacity higher than 98% for Cd, Cr and As. These results suggest that nHCV can be used as an efficient adsorbent for heavy metals removal from contaminated water sources